Altered resting-state functional connectivity of default mode network in brachioradial pruritus - Dehghan Nayyeri, Mahboobeh; Mißler-Behr, Magdalena; Ritterbach, R.; Sundermann, B.; Wulms, N.; Süer, A.; Dugas, M.; Pereira, M. P.; Ständer, S.; Schmelz, Martin; Pfleiderer, Bettina (Journal of the European Academy of Dermatology and Venereology, 2022)
Background Patients with chronic pruritus (CP) have a low quality of life, thus it is important to gain a better understanding of the underlying processes. Previous functional magnetic resonance imaging studies at rest (rsfMRI) have shown that mainly areas associated with the default mode network (DMN), sensorimotor (SMN), frontoparietal (FPN) and salience networks (SN) are involved in the processing of itch in patients with chronic pruritus (CP), as well as the cortico-striatal circuit, which is involved in the motoric preparation of scratching. rsfMRI studies on functional connectivity (FC) patterns of resting-state networks (RSNs) in patients with inflammatory atopic dermatitis (AD) or with neuropathic brachioradial pruritus (BRP) compared with healthy controls (HC) are lacking. Objectives The main goals of this study were to investigate whether functional connectivity within networks and areas associated with itch detection and processing are altered in patients with AD and BRP compared with matched healthy controls by rsfMRI, respectively. Methods Patients with AD (n = 28) and with BRP (n = 28) were compared with corresponding matched healthy controls by rsfMRI. Group-specific RSNs were identified by independent component analysis (ICA) and between-group differences in the RSNs were analysed by dual regression technique. Seed-based functional connectivity was analysed in several itch-related brain regions belonging to the DMN, SN and FPN, respectively. Results ICA and seed-based analyses revealed decreased functional connectivity in BRP compared with HC specially within the DMN including the precuneus and cingulate cortex. For AD patients in comparison with HC, as well as when BRP and AD patients were compared directly, no significant FC differences at rest were seen. Conclusions Our findings point towards decreased FC particularly in the DMN at rest in patients with BRP. These results seem to indicate that central connectivity patterns at rest differentially encode itch in BRP and AD.
Gesehen am 24.07.2023